صدام الثقافات: قراءة جديدة في رواية فورستر "الطريق إلى الهند" ورواية كونراد "قلب الظلام" (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study deals with the conflict between civilizations. It takes Forster’s A Passage to India and Conrad’s Heart of Darkness as examples to illustrate this phenomenon. In A Passage to India the conflict between the British culture and the Indian culture is manifested in various forms. To demonstrate these differences, Forster presents a wide range of elements particular to each culture. He includes not only people of the two countries as part of the conflict, but also other elements relating to the general make-up of the cultural and environmental context of the two countries. Fielding and Dr. Aziz wish that their friendship might continue, but “the horses didn’t want it – they swerved apart,” and “the earth didn’t want it, sending up rocks through which riders must pass single file” (Forster, p. 289). This refusal to conciliate, however, seems to be the result of “the whole conflict of civilizations” (Crews, p. 168). Conrad in his Heart of Darkness highlights the disparity between the Western culture and the African culture by referring to the cultural and dogmatic differences that separate the two cultures. In the novel we stand before a social panorama in which the blame for the failure of communication rests, as is the case in A Passage to India, not only on “the whole conflict of civilizations,” but also on the fundamental differences in social structure, religious outlook and temperament. The study comes to the conclusion that bridging the gap between the social and cultural structures of two different nations cannot be brought about by use of force, “intimidation”, “extermination”, or submission of the so-called less civilized nations. Similarly, the question of compromise between cultures can be effected only by creating harmony between cultures, rather than integration and annihilation of one culture on the account of the other. Thus, removing the cultural and social barriers between different cultures inevitably demands obliterating the causes which bring about such divisions. Hence, it becomes necessary, in Mrs. Moore’s opinion, that conciliation between two different nations requires fulfillment of God’s will on earth which recommends that “God has put us on the earth in order to be pleasant to each other” (Forster, p. 64).     يعالج البحث موضوع الصراع الذي تمتد جذوره الى عصور موغلة بالقدم. فالصراع الحضاري في رواية "الطريق الى الهند" يتجسد في عدد من الاختلافات الثقافية, والفكرية, والدينية, والعقائدية وغيرها. وتبرز هذه الاختلافات جلية في الصراع بين مجتمعين, مجتمع غربي متعال في نظرته, متميز في أسلوب حياة أبنائه, وعاداته وتقاليده, ومجتمع شرقي محافظ في عاداته وتقاليده ومفاهيمه للحياة, والدين, والمجتمع. ومن هنا يأتي الصدام بين المجتمعين, حيث يقف الدكتور عزيز, بطل القصة، عاجزا عن رأب الصدع بين هذين العالمين المتنافرين, على الرغم الجهود المخلصة التي يبذلها في هذا السياق. يحال عزبز إلى المحكمة بتهمة الاعتداء الجنسي على عديلا كويستد, على الرغم من براءته, ثم يتبين لاحقا, بعد صحوة ضمير عديلا, بأن الحادث الذي وقع في كهوف مرابار في مدينة تشاندرابور, كان عرضيا. يعلق  ﺇ. م. فورستر في تهاية الرواية على ظاهرة صدام الحضارات بقوله أن جذور المشكلة تكمن ليس في المجتمعات فحسب وﺇنما بطبيعة المكان, والأرض, والطبيعة بشتى صورها وأشكالها التي يبدو أنها تأبى مثل هذا اللقاء. أما رواية كونراد "قلب الظلام" فتصور هذا الصراع  بين عالمين متناقضين تماما: عالم غربي يدعي الحضارة, ويقوم على أسس ﺇاستعمارية بحتة, وعالم ﺇفريقي متخلف, بدائي يقوم على الصيد البري بقصد جمع العاج. يأتي الغربيون إلى الكونغو تحت راية تحرير المجتمع اﻹفريقي البدائي من التخلف والجهل, ولكن هذا الشعار لا يلبث طويلا حتى ينقلب إلى نقيض ما جاء به. فيتحول المحررون إلى مستعمرين, وعصابات تقوم على سلب ونهب العاج الإفريقي, متناسين الهدف الذي جاؤوا من أجله. يلجأ المستعمرون لتحقيق هذا الهدف إلى استعباد من جاء تحت قبضتهم من الأفارقة, ليبدأ الصراع بين عالمين متناقضين, عالم ﺇفريقي تحكمه القبيلة, والسحر, والعادات القبلية, والخرافات, وآخر غربي يحكمه الجشع, والرغبة في استعباد الآخر بقصد جمع الثروات. يصطدم العالمان, ويتنافر المجتمعان, وتنهار العلاقات بين المجتمعين, ولا يبقى ما يربط المجتمعين من شيء, بحيث يصبح الانفصال بينهما, كما هو الحل في رواية فورستر, أمرا لابد منه. يخلص البحث إلى نتيجة واضحة, بعد عرض مفصل لهاتين الظاهرتين المشار ﺇليهما أعلاه في رواية فورستر وكونراد, بأن التقارب بين الحضارات لا يمكن أن يتحقق ﺇلا من خلال حوار بناء, يقوم على أسس واضحة من المساواة والعدالة, واحترام متبادل لمصالح كل من الطرفين المتحاورين؛ كما أن استمرار هذا الحوار رهن باحترام حقوق الطرفين السيادية, والمادية, والثقافية, والفكرية, والدينية, والاعتبارية وغيرها, وﺇلا فأن الفشل وزيادة الفرقة بين الحضارات سيكون هو المآل.